Influence of different host plants on growth and development of the gypsy moth larvae LymantriadisparL (Lepidoptera: Lymantriidae). - Ramadan, Ali; saleh, Ali (Latakia University Journal -Biological Sciences Series, 2013)
Gypsy moth (Lymantriadispar) is polyphagous insect .Therefore we had conducted an experiment to determine the influence of the following plant hosts(Malussp, Quercussp ,Prunus. armeniaca, Platanusprientalis, Pinusnigra) onthe growth and development of gypsy moth's larvae. The results showed that duration of larval development was the longest onPinusnigra(77,1±5,46) days and the shortest on Malussp(37,5±4,96) days,for larval growth in length and weight larvae had gained the higher length and weight on Malussp in the order (62±1,9)m.m (2136±9,62) mg. on the other hand the lower length and weight were on Pinusnigra in the order (38±2,44)m.m (545±7,91) m.g. mortality percent of larvae was least on Malussp.and highest on Pinusnigra. Finally, pupae had the best weight with shortest development duration on the Malussp, while the least weight and longest development duration were on the Pinusnigra. There were proportional indirect of larval percentage mortality on relation to plant host, it was highest on lower preference plant